The bookstore on the beach [large type] - Novak, Brenda (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"Autumn takes her kids home for the summer to the charming beachside town where she was raised. She seeks comfort working alongside her mother and aunt at their bookshop ... And when she runs into the boy who stole her heart in high school, old feelings start to bubble up again. Is she free to love him, or should she hold out hope for her husband's return? She can only trust her heart and hope it won't lead her astray"--